Black ceramic metal coated glass and method of making the same
Patent Information
- Application Number
- CN202510477107.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-16
- Publication Date
- 2026-10-23
AI Technical Summary
但是,问题在于,这些特定的黑色陶瓷材料往往难以在加热玻璃的同时使用模具进行弯曲成形以及在烧成黑色陶瓷材料后进行脱模,从而增加黑色陶瓷金属涂层玻璃的生产难度
[0051]根据本发明,能够提供一种黑色陶瓷金属涂层玻璃,其可以在消除红色光晕现象的同时保持良好的脱模性。根据本发明,还能够提供这种黑色陶瓷金属涂层玻璃的生产方法以及由此制成的夹层玻璃。
Smart Images

Figure HDA0005361663840000011 
Figure HDA0005361663840000012
Abstract
Description
Technical Field
[0001] This invention relates to a black ceramic-metal coated glass and its manufacturing method. Background Technology
[0002] In the modern glass manufacturing industry, metallic-coated glass is widely used in many fields such as electronic display devices, architectural glass, and automotive glass due to its excellent electrical conductivity, optical properties, and decorative effects. For example, in the automotive glass industry, silver-coated glass is often used for windshields and sunroofs, and its silver coating can effectively block solar heat and improve the comfort of the car interior.
[0003] On the other hand, automotive glass typically has a black ceramic layer on its surface, usually distributed near the perimeter of the glass. This black ceramic layer can be used to shield electrical and other connecting components located around the inner surface of the glass, thus improving the vehicle's appearance.
[0004] However, in metallic-coated glass, especially silver-coated glass, the contact between the traditional black ceramic and the silver coating can lead to a red haze phenomenon. Red haze is a red optical defect that appears at the interface between silver and black ceramic in silver-coated glass. This phenomenon not only affects the appearance of the glass but can also reduce its optical performance.
[0005] To effectively eliminate the red halo effect, research has shown that certain black ceramic materials do not produce a noticeable red halo even when in contact with a silver coating. However, the problem lies in the fact that these specific black ceramic materials are often difficult to bend and shape using molds while heating the glass, and difficult to demold after firing, thus increasing the difficulty of producing black ceramic-metal coated glass.
[0006] Therefore, for black ceramic metal-coated glass, traditional methods cannot simultaneously solve the problems of red halo phenomenon and poor release properties, because these two properties have contradictory requirements for black ceramic materials. Summary of the Invention
[0007] The technical problem that the invention aims to solve
[0008] This invention provides a black ceramic-metal coated glass that maintains good release properties while eliminating red halo effects. The invention also provides a method for producing this black ceramic-metal coated glass and laminated glass made from it.
[0009] Technical solutions adopted to solve technical problems
[0010] The present invention has the following technical content.
[0011] Form 1
[0012] A glass plate comprising
[0013] Glass motherboard,
[0014] First ceramic layer
[0015] Contains metal layer,
[0016] Second ceramic layer,
[0017] Wherein, the metal is silver or a mixture of silver and other metals.
[0018] The first ceramic layer and the second ceramic layer at least partially overlap when viewed from above.
[0019] The first ceramic layer contains Bi4Si3O 12 The crystallization ratio of CuCrMnO4, as determined by XRD, ranged from 0.1% to 8.0%.
[0020] The second ceramic layer is located on the side of the first ceramic layer opposite to the glass substrate, and contains Bi4Si3O. 12 The crystallization ratio of CuCrMnO4, as determined by XRD, was 9.5–30.0%.
[0021] The crystallization ratio is Bi4Si3O 12 The ratio of CuCrMnO4.
[0022] Form 2
[0023] The glass plate as described in form 1, wherein the crystallinity of the first ceramic layer is 0.1 to 5.0%, and the crystallinity of the second ceramic layer is 10.0 to 25.0%.
[0024] Form 3
[0025] The glass plate as described in form 1 or 2, wherein, when viewed from above, the metal-containing layer does not overlap with the second ceramic layer.
[0026] Form 4
[0027] The glass plate as described in form 1 or 2, wherein, when viewed from above, the metal-containing layer at least partially overlaps with the second ceramic layer, and the inner edge of the overlapping portion is located more than 10 mm outside the inner edge of the first ceramic layer.
[0028] Form 5
[0029] The glass plate as described in any one of forms 1 to 4, wherein the width of the first ceramic layer is 10 mm or more.
[0030] Form 6
[0031] The glass plate as described in any one of forms 1 to 5, wherein the width of the second ceramic layer is 5 mm or more.
[0032] Form 7
[0033] The glass plate as described in any one of forms 1 to 6, wherein the metal is silver.
[0034] Form 8
[0035] The glass plate as described in any one of forms 1 to 7, wherein the metal-containing layer comprises two or more layers of metal made of silver.
[0036] Form 9
[0037] A laminated glass having a glass plate as described in any one of forms 1 to 8, a second glass plate, and an interlayer film located between the glass plate and the second glass plate and joining the two glass plates.
[0038] Form 10
[0039] The laminated glass as described in form 9, wherein the visible light transmittance of the laminated glass is less than 10%.
[0040] Form 11
[0041] A method for manufacturing a glass plate according to any one of forms 1 to 8, comprising the following steps:
[0042] 1) The process of providing glass motherboards;
[0043] 2) The step of applying a first ceramic raw material composition comprising at least bismuth oxide, silicon oxide and Cr2CuO4 to at least a portion of a glass master plate;
[0044] 3) The process of firing to form the first ceramic layer;
[0045] 4) The process of forming a metal layer:
[0046] 5) The step of applying a second ceramic raw material composition comprising at least bismuth oxide, silicon oxide and Cr2CuO4 to at least a portion of the first ceramic layer;
[0047] 6) The process of firing to form the second ceramic layer.
[0048] Form 12
[0049] The manufacturing method as described in aspect 11, wherein the firing temperature is 600–670°C.
[0050] Invention Effects
[0051] According to the present invention, a black ceramic-metal coated glass can be provided that maintains good release properties while eliminating red halo phenomena. The present invention also provides a method for producing such a black ceramic-metal coated glass and laminated glass made therefrom.
[0052] Other aspects, features and advantages of the invention will become apparent in the following detailed description. Brief description of the attached figures
[0053] Figure 1 The diagram shown is a cross-sectional view of a glass plate according to one embodiment of the present invention in a top view.
[0054] Figure 2 The diagram shown is a cross-sectional view of a glass plate according to another embodiment of the present invention in a top view.
[0055] The numerical values in the attached figures are for illustrative purposes only and are not intended to be restrictive. Detailed Implementation
[0056] The following terms in this specification have the following meanings.
[0057] "Top view" refers to viewing a specified area from the direction of its normal. Unless otherwise stated, "top view" simply means viewing a glass plate (or laminated glass) from the direction of its normal. Planar shape refers to the shape of a specified area when viewed from the direction of its normal.
[0058] When viewed from above, "inner side" refers to the side of the glass plate surface closer to the center, and "outer side" refers to the side of the glass plate surface closer to the perimeter.
[0059] glass plate
[0060] According to one embodiment of the present invention, a glass plate (hereinafter referred to as "this glass plate") is provided, comprising a glass substrate, a first ceramic layer, a metal-containing layer, and a second ceramic layer. Furthermore, as needed, this glass plate may further comprise other layer structures known in the art.
[0061] (Glass motherboard)
[0062] The composition of the glass substrate is not particularly limited. The glass substrate can be inorganic glass or organic glass, such as soda-lime glass, aluminosilicate glass, borosilicate glass, or alkali-free glass, but inorganic glass is preferred.
[0063] The thickness of the glass master sheet is not particularly limited, and generally falls within the range of 0.1 mm to 20 mm, which can be appropriately selected according to the actual application. For example, when this glass sheet is used for automotive glass, from the viewpoint of resistance to flying stone impacts, the thickness of the glass master sheet is preferably 0.3 mm or more, more preferably 0.5 mm or more, further preferably 1.0 mm or more, and particularly preferably 1.5 mm or more. In addition, in order to suppress the weight of automotive glass, the thickness of the glass master sheet is preferably 10.0 mm or less, more preferably 8.0 mm or less, and further preferably 6.0 mm or less. Furthermore, when the glass master sheet is used in composite glass, the thickness of the glass master sheet is preferably 4.0 mm or less, more preferably 3.0 mm or less, and further preferably 2.5 mm or less.
[0064] Glass master sheets typically have curved shapes. Curved shapes include so-called "single-curve" shapes where the glass has curvature in one direction and so-called "multi-curve" shapes where the glass has curvature in two orthogonal directions. However, this is just one example; glass master sheets can also be flat.
[0065] The glass substrate has two main surfaces facing each other, namely a first surface and a second surface. For example, in the case where this glass substrate is used for automotive glass, the first surface is the interior side of the vehicle, and the second surface is the exterior side of the vehicle.
[0066] (Including a metal layer)
[0067] The metal containing the metal layer can be silver, gold, palladium, platinum, etc. In one specific embodiment, the metal is silver. In another specific embodiment, the metal is a mixture of silver and other metals such as gold, palladium, and platinum.
[0068] The metal layer can be directly applied to the first and / or second surfaces of the glass substrate, or it can be applied to the first and / or second surfaces of the glass substrate separately from other layers. For example, in the case where this glass substrate is used for automotive glass, by applying the metal layer to the glass substrate, solar heat can be effectively blocked, improving in-vehicle comfort.
[0069] The thickness of the metal layer is not particularly limited, for example, it can be in the range of 100nm to 500nm, preferably 150nm to 400nm, and more preferably 170nm to 300nm.
[0070] The metal-containing layer can be a single layer or multiple layers, but multiple layers are preferred. In a particular embodiment, the metal-containing layer comprises two or more layers. When the metal-containing layer comprises two or more layers, the chemical composition of each layer can be the same or different. For example, in a particular embodiment, the metal-containing layer comprises two or more layers composed of silver. For example, in a particular embodiment, the metal-containing layer comprises a layer containing a tin oxide compound or a layer composed of a silicon nitride compound, referred to as a dielectric layer.
[0071] When viewed from above, the metal layer can cover the entire area of the glass substrate or only a portion of it. When the metal layer covers only a portion of the glass substrate, the distance between the edge of the metal layer and the edge of the glass substrate can be, for example, 10 mm or more, preferably 15 mm or more, and more preferably 20 mm or more.
[0072] (First ceramic layer)
[0073] The first ceramic layer can be opaque, but it only needs to block visible light to a degree that allows for concealment, at least in the areas requiring concealment. For example, the first ceramic layer can be made of colored ceramic materials. The first ceramic layer is usually black, but it can also be dark colors such as brown, gray, or navy blue.
[0074] The thickness of the first ceramic layer is not particularly limited, for example, it can be in the range of 1μm to 30μm, preferably 2μm to 20μm, more preferably 5μm to 17μm, and even more preferably 5μm to 10μm.
[0075] The first ceramic layer may be located on the first and / or second surfaces of the glass substrate, and is distributed on the outer periphery of the first and / or second surfaces. In one particular embodiment, the first ceramic layer is distributed on all edges of the first and / or second surfaces of the glass substrate. In another particular embodiment, the first ceramic layer is distributed on a portion of the edges of the first and / or second surfaces of the glass substrate. The first ceramic layer may be directly disposed on the first and / or second surfaces of the glass substrate, or it may be disposed on the first and / or second surfaces of the glass substrate, spaced apart from other layers. For example, when this glass panel is used for automotive glass, by providing the first ceramic layer on the first and / or second surfaces, the deterioration of bonding components such as urethane resin used when bonding this glass panel (or laminated glass) to a vehicle due to ultraviolet radiation, etc., can be suppressed. Furthermore, the first ceramic layer can be used to shield electrical and other connecting components located around the inner surface of the glass, thereby improving the appearance of the vehicle.
[0076] The width of the first ceramic layer is typically 10 mm or more, preferably 12 mm or more, and more preferably 14 mm or more. Width refers to the shortest distance from the inner edge to the outer edge when viewed from above. The width of the first ceramic layer is preferably less than 100 mm. If the width of the first ceramic layer is above the lower limit, it provides sufficient shielding. If the width of the first ceramic layer is below the upper limit, the driver's view can be ensured to remain unobstructed.
[0077] Viewed from above, the first ceramic layer partially overlaps with the metal-containing layer. This is because the first ceramic layer of the present invention does not cause a noticeable red halo even when in contact with the metal-containing layer, thus allowing it to contact the metal-containing layer. Furthermore, if the first ceramic layer contacts the metal-containing layer, there will be no gap between the first ceramic layer and the silver-containing layer, ensuring good aesthetics. In a specific embodiment, the width of the overlapping portion of the first ceramic layer and the metal-containing layer is preferably in the range of 5 mm to 90 mm, more preferably in the range of 35 mm to 85 mm.
[0078] The first ceramic layer contains Bi4Si3O 12 The crystallization ratio of CuCrMnO4, as determined by XRD, is 0.1–8.0%, wherein the crystallization ratio is Bi4Si3O. 12 The ratio of CuCrMnO4 is preferred. The crystallization ratio is preferably 6.0% or less, more preferably 5.0% or less, even more preferably 3.0% or less, even more preferably 2.0% or less, and most preferably 1.0% or less. If the crystallization ratio of the first ceramic layer is below the upper limit, a red halo phenomenon is less likely to occur even if the first ceramic layer partially overlaps with the metal-containing layer.
[0079] (Second ceramic layer)
[0080] The second ceramic layer can be opaque, but it only needs to block visible light to a sufficient degree in areas requiring concealment. For example, the second ceramic layer can be made of colored ceramic materials. The second ceramic layer is typically black, but it can also be dark colors such as brown, gray, or navy blue. The color of the second ceramic layer can be the same as or different from the first ceramic layer.
[0081] The thickness of the second ceramic layer is not particularly limited, for example, it can be in the range of 1μm to 30μm, preferably 2μm to 20μm, and more preferably 3μm to 15μm. The thickness of the second ceramic layer can be the same as or different from that of the first ceramic layer.
[0082] The combined thickness of the first ceramic layer and the second ceramic layer can be in the range of 2μm to 50μm, preferably 5μm to 20μm, and more preferably 10μm to 15μm.
[0083] The second ceramic layer is located on the same side of the glass substrate as the first ceramic layer, but is disposed on the opposite side of the first ceramic layer. The second ceramic layer can be directly disposed on the first ceramic layer, or it can be disposed on the first ceramic layer, separated from other layers. Similar to the first ceramic layer, for example, in the case where this glass panel is used for automotive glass, by further providing the second ceramic layer, the degradation of the urethane resin used when bonding this glass panel (or laminated glass) to the vehicle due to ultraviolet radiation and other factors can be better suppressed. Furthermore, the second ceramic layer can also be used to shield electrical and other connecting components located around the inner surface of the glass, thereby improving the vehicle's appearance.
[0084] The second ceramic layer contains Bi4Si3O 12 The crystallization ratio of CuCrMnO4, as determined by XRD, was 9.5–30.0%, wherein the crystallization ratio was Bi4Si3O. 12 The ratio of CuCrMnO4 is preferred. The crystallinity ratio is preferably 10.0% or higher, more preferably 12.0% or higher, even more preferably 14.0% or higher, even more preferably 16.0% or higher, and most preferably 18.0% or higher. If the crystallinity ratio of the second ceramic layer is above the lower limit, sufficient demolding properties can be achieved during the manufacturing process of the glass plate. The crystallinity ratio is preferably 25.0% or lower. The crystallinity ratio of the second ceramic layer is greater than that of the first ceramic layer.
[0085] The width of the second ceramic layer is typically 5 mm or more, preferably 6 mm or more, and more preferably 7 mm or more. Width refers to the shortest distance from the inner edge to the outer edge when viewed from above. The width of the second ceramic layer is preferably less than 40 mm, and more preferably less than 15 mm. If the width of the second ceramic layer is above the lower limit, it can provide sufficient release properties during the glass manufacturing process. If the width of the second ceramic layer is below the upper limit, it ensures that the driver's view is not obstructed and that a red halo effect is less likely to occur within the driver's field of vision.
[0086] In one implementation, such as Figure 1 As shown, when viewed from above, the second ceramic layer does not overlap with the metal-containing layer. If the second ceramic layer does not overlap with the metal-containing layer, no red halo phenomenon will occur.
[0087] In one implementation, such as Figure 2As shown, when viewed from above, the second ceramic layer partially overlaps with the metal-containing layer. In this case, to ensure that the resulting red halo effect does not fall within the driver's line of sight, the inner edge of the overlapping portion is located at least 10 mm outside the inner edge of the first ceramic layer. In embodiments where the second ceramic layer partially overlaps with the metal-containing layer, the inner edge of the overlapping portion is preferably located at least 11 mm outside the inner edge of the first ceramic layer, more preferably at least 12 mm outside the inner edge of the first ceramic layer, still more preferably at least 15 mm outside the inner edge of the first ceramic layer, and most preferably at least 20 mm outside the inner edge of the first ceramic layer.
[0088] Manufacturing method of glass plate
[0089] According to one embodiment of the present invention, a method for manufacturing a glass plate is provided, comprising the following steps:
[0090] 1) The process of providing glass motherboards;
[0091] 2) The step of applying a first ceramic raw material composition comprising at least bismuth oxide, silicon oxide and Cr2CuO4 to at least a portion of a glass master plate;
[0092] 3) The process of firing to form the first ceramic layer;
[0093] 4) The process of forming a metal layer:
[0094] 5) The step of applying a second ceramic raw material composition comprising at least bismuth oxide, silicon oxide and Cr2CuO4 to at least a portion of the first ceramic layer;
[0095] 6) The process of firing to form the second ceramic layer.
[0096] In addition to containing bismuth oxide, silicon oxide, and Cr2CuO4, ceramic raw material compositions may also contain glass frit, pigments, and other additives.
[0097] Depending on the desired properties of the ceramic layer, the glass frit can contain varying amounts of oxides of silicon, niobium, sodium, boron, zinc, bismuth, titanium, molybdenum, zirconium, yttrium, aluminum, lithium, and potassium. These oxides can provide various functions to the first ceramic layer, such as network formation, flux composition, melting point control, firing temperature control, chemical durability improver, migration inhibitor, gloss suppressant, and water repellency. Typically, oxides will be used in specific and known amounts to provide the desired properties.
[0098] Examples of seed materials constituting the base of glass frits include zinc borate, zinc silicate, zinc titanate, bismuth silicate, aluminum silicate, and mixtures thereof. Therefore, glass frits can be zinc-based, bismuth-based, bismuth-free, or other types.
[0099] Glass frits can be formed by blending and melting materials at temperatures ranging from 950°C to 1350°C for 30 to 60 minutes to form molten glass of a given composition. The molten glass can then be cooled using any suitable technique to form glass frits, which can then be ground into fine particles ranging from 1 to 8 μm.
[0100] Pigments can include metal oxides, such as oxides of chromium, cobalt, copper, nickel, manganese, and iron. Pigments can further include inorganic pigments, especially olivine, andalusite, borates, pyrochlore, sphene, and hematite.
[0101] Other additives may include tackifiers, seed crystals, reducing agents, conductive metals (such as silver particles), rheology modifiers, flow aids, tackifiers, stabilizers, etc.
[0102] In the process of firing the first ceramic layer, a ceramic raw material composition is adhered to the surface of a glass substrate at a temperature of 550°C to 700°C to form the fired first ceramic layer. The firing temperature can alternatively range from 600°C to 650°C. The duration of the firing process can be 120 to 600 seconds. Under these firing conditions, the first ceramic layer can be satisfactorily fired while maintaining its crystallinity within a suitable range.
[0103] After the first ceramic layer is fired, a metal-containing layer is applied to form a metal-coated glass plate. The metal-containing layer can be formed by deposition. Typical deposition methods include CVD, PECVD, PVD, magnetron sputtering, and wet coating; however, PECVD, PVD, and magnetron sputtering are preferred for their ability to create multiple nanoscale thin layers. Furthermore, different metal-containing layers can be deposited using different techniques.
[0104] A metal-containing layer is deposited on at least a portion of a first surface and / or a second surface of a glass substrate, and simultaneously deposited on at least a portion of a sintered first ceramic layer to form a coated glass substrate. The metal-containing layer may be in direct contact with the first ceramic layer.
[0105] The metal-containing layer can be deposited on the entire first and / or second surface of the glass substrate, including areas without the first ceramic layer and areas with the first ceramic layer. In one particular embodiment, the metal-containing layer may not cover the entire first and / or second surface of the glass substrate where the first ceramic layer is present. The boundaries of the first and / or second surfaces where the first ceramic layer is present may be free of the metal-containing layer. Such boundary areas without the metal-containing layer can prevent damage or corrosion of the metal-containing layer during glass cutting or mounting.
[0106] The metal layer can be uniform across the entire surface of the glass substrate or it can be divided into multiple sections. That is, the entire surface of the glass substrate can be divided into multiple sections, some of which have the metal layer and some of which do not.
[0107] The metal-containing layer may or may not be conductive. When the metal-containing layer is conductive, it includes at least one conductive functional layer, which can be a metal (metal functional layer) or a conductive oxide layer (doped metal oxide). When the metal-containing layer is non-conductive, it can be a metal-containing layer without a metal functional layer or a metal-containing layer without a conductive oxide. The functional layer may not necessarily serve as a conductive layer; that is, the conductivity of the metal-containing layer may or may not be necessary in the final application. For example, in architectural applications, the metal-containing layer may primarily provide solar control or thermal radiation control characteristics, while in automotive applications, it can be used as a solar control coating, but it can also be used as a conductive coating for heated windshields.
[0108] The process of firing the second ceramic layer is completed under the same conditions as the process of firing the first ceramic layer.
[0109] Laminated glass
[0110] According to one embodiment of the present invention, the present invention provides a laminated glass (hereinafter referred to as "the laminated glass") having a primary glass plate, a second glass plate, and an interlayer film located between the primary glass plate and the second glass plate and bonding the two glass plates.
[0111] (Second glass plate)
[0112] The composition of the second glass plate may be the same as or different from that of the first glass plate. Furthermore, the second glass plate may have a different thickness than the first glass plate.
[0113] The second glass plate can be located on different main surface sides of the main glass plate. For example, in the case where the main glass plate is used for automotive glass, the second glass plate can be located on the outer side of the main glass plate or the inner side of the main glass plate. The main glass plate, the second glass plate, and the interlayer film are stacked on top of each other in an opposing manner.
[0114] In addition, the second glass plate can have functional films such as low-emissivity film and low-reflection film on the main surface.
[0115] The thickness of the second glass plate is preferably 4.0 mm or less, more preferably 3.0 mm or less, and even more preferably 2.5 mm or less. The thickness of the second glass plate may be the same as or different from that of the first glass plate.
[0116] (Intermediate membrane)
[0117] Intermediate films are typically made of resin. For example, they can be made of thermoplastic resins, thermosetting resins, or photocurable compositions. Examples of thermoplastic resins include plasticized polyvinyl acetal resins, plasticized polyvinyl chloride resins, saturated polyester resins, plasticized saturated polyester resins, polyurethane resins, plasticized polyurethane resins, ethylene-vinyl acetate copolymer resins (EVA), cyclic olefin polymer resins (COP), and ethylene-ethyl acrylate copolymer resins. Furthermore, resin compositions containing modified block copolymer hydrogenates as described in Japanese Patent No. 6065221 can also be used.
[0118] Among them, plasticized polyvinyl acetal resin and EVA are preferred. This is because plasticized polyvinyl acetal resin and EVA have excellent balance in various properties such as transparency, weather resistance, strength, adhesion, impact energy absorption, moisture resistance, heat insulation and sound insulation.
[0119] In addition, the term "plasticized" in plasticized polyvinyl acetal resins means that plasticization can be achieved by adding plasticizers. The same meaning applies to other plasticized resins.
[0120] The aforementioned thermoplastic resins can be used alone or in combination of two or more.
[0121] Examples of polyvinyl alcohol acetal resins include polyvinyl alcohol formaldehyde resins obtained by reacting polyvinyl alcohol (PVA) with formaldehyde, polyvinyl alcohol acetal resins (in the narrow sense) obtained by reacting PVA with acetaldehyde, and polyvinyl alcohol butyral resins (PVB) obtained by reacting PVA with n-butyraldehyde. In particular, PVB is preferred from the viewpoint of achieving an excellent balance of various properties such as transparency, weather resistance, strength, adhesion, penetration resistance, impact energy absorption, moisture resistance, thermal insulation, and sound insulation. These polyvinyl alcohol acetal resins can be used alone or in combination of two or more types.
[0122] The intermediate membrane may also contain functional particles such as infrared absorbers, ultraviolet absorbers, colorants, and luminescent agents.
[0123] Furthermore, the interlayer can consist of two or more layers. For example, by making the interlayer consist of three layers and making the hardness of the central layer lower than that of the two side layers, sound insulation can be improved. In this case, the hardness of the two side layers can be the same or different.
[0124] The thickness of the interlayer is, for example, 0.3 mm or more at its thinnest point and less than 3 mm at its thickest point. Maintaining a thickness of 0.3 mm or more improves impact resistance. Furthermore, maintaining a thickness of less than 3 mm helps control the quality of the laminated glass.
[0125] (Visible light transmittance of this laminated glass)
[0126] The visible light transmittance of this laminated glass is below 20%. Visible light transmittance can be measured according to Japanese Industrial Standard JIS R3106:2019. If the visible light transmittance of this laminated glass is below the upper limit, a red halo phenomenon is less likely to occur according to the present invention. Preferably, the visible light transmittance of this laminated glass is below 15%, more preferably below 10%, even more preferably below 5%, even more preferably below 3%, and most preferably below 2%.
[0127] Generally, the lower the visible light transmittance of laminated glass, the easier it is to detect the red halo phenomenon. Surprisingly, the inventors have cleverly designed the glass panels constituting the laminated glass to ensure that, even with low transmittance, the red halo phenomenon is not easily observed within the driver's line of sight. The same applies to the visible light transmittance when the glass panel is used as a single pane of glass for windows, rather than as laminated glass.
[0128] Applications of this glass sheet and this laminated glass
[0129] This glass sheet, this laminated glass, can be used with any suitable glass material in the transportation field. The transportation field includes automobiles and various other means of transportation, such as ships, trains, airplanes, spacecraft, and space stations.
[0130] Example
[0131] The present invention will be described in more detail below based on embodiments, but the present invention is not limited to these embodiments.
[0132] The following shows the determination or test methods and materials used in each example.
[0133] The crystallinity ratio of the ceramic layer was calculated using XRD (X-ray diffraction). The apparatus used was the Rigaku Smart Lab, a fully automated multi-functional X-ray diffraction system. The sample was cut to a size (a few centimeters square) suitable for storage on the sample stage of the apparatus and placed inside. Measurement conditions (tube voltage 45 kV, tube current 200 mA) were input, and measurements were performed using the 2θ / θ scanning method at measurement angles of 10°–80°, intervals of 0.02°, and a scanning speed of 20° / min. Using the obtained x-axis 2θ / θ angle and y-axis CPS (counts per second) values, the crystallinity ratio of the ceramic layer (Bi4Si3O) was calculated. 12 CPS (counts per second) of the crystal phase / CPS (counts per second) of the CuCrMnO4 crystal phase. Additionally, Bi4Si3O 12The peak of the (crystalline phase) was obtained at 2θ / θ: 32.6°, and the peak of CuCrMnO4 (spinel pigment phase) was obtained at 2θ / θ: 35.8°.
[0134] The glass substrate is made of Taiwan Glass Qingdao 1.6 1# type glass manufactured by Taiwan Glass Qingdao Glass Co., Ltd., with a thickness of 1.6mm and a melting point of 727.5℃.
[0135] The XRD determination of the crystallinity of the first ceramic layer 1 was 4.7%. The XRD determination of the crystallinity of the second ceramic layer 1 was 22.6%, and the XRD determination of the crystallinity of the second ceramic layer 2 was 10.4%.
[0136] (Glass plate preparation method)
[0137] After screen printing the first ceramic layer on a glass master plate, it is fired at 630°C. Then, a silver-containing layer, including two silver layers and a dielectric layer, is formed using sputtering. Further, after screen printing the second ceramic layer, the ceramic layer is placed in a stainless steel mold and fired at 630°C.
[0138] (Example 1)
[0139] A glass plate 1 is formed by stacking a first ceramic layer 1, a silver-containing layer, and a second ceramic layer 1 on a glass mother plate. In the glass plate 1, the outer edges of the first ceramic layer 1 and the second ceramic layer 1 overlap. The width of the first ceramic layer 1 is 20 mm, and the width of the second ceramic layer 1 is 10 mm. The width of the overlap between the silver-containing layer and the first ceramic layer 1 is 9.9 mm.
[0140] (Example 2)
[0141] A glass plate 2 is formed by stacking a first ceramic layer 1, a silver-containing layer, and a second ceramic layer 2 on a glass mother plate. In the glass plate 2, the outer edges of the first ceramic layer 1 and the second ceramic layer 2 overlap. The width of the first ceramic layer 1 is 19 mm, and the width of the second ceramic layer 2 is 10 mm. The overlap between the silver-containing layer and the first ceramic layer 1 is 2 mm wide.
[0142] (Example 3)
[0143] A glass plate 3 is formed by stacking a first ceramic layer 1, a silver-containing layer, and a second ceramic layer 1 on a glass mother plate. In the glass plate 3, the outer edges of the first ceramic layer 1 and the second ceramic layer 1 overlap. The width of the first ceramic layer 1 is 21 mm, and the width of the second ceramic layer 1 is 11 mm. The width of the overlap between the silver-containing layer and the first ceramic layer 1 is 11 mm.
[0144] (Comparative Example 1)
[0145] A glass plate 4 is formed by stacking a first ceramic layer 1, a silver-containing layer, and a second ceramic layer 1 on a glass mother plate. In the glass plate 4, the outer edges of the first ceramic layer 1 and the second ceramic layer 1 overlap. The width of the first ceramic layer 1 is 19 mm, and the width of the second ceramic layer 1 is 10.1 mm. The width of the overlap between the silver-containing layer and the first ceramic layer 1 is 9 mm.
[0146] (Comparative Example 2)
[0147] A glass plate 5 is formed by stacking a first ceramic layer 1, a silver-containing layer, and a second ceramic layer 1 on a glass mother plate. In the glass plate 5, the outer edges of the first ceramic layer 1 and the second ceramic layer 1 overlap. The width of the first ceramic layer 1 is 20 mm, and the width of the second ceramic layer 1 is 10 mm. The silver-containing layer and the first ceramic layer 1 do not overlap.
[0148] (Comparative Example 3)
[0149] A glass plate 6 is formed by stacking a first ceramic layer 1 and a silver-containing layer on a glass mother plate. In the glass plate 6, the width of the first ceramic layer 1 is 20 mm. The width of the overlap between the silver-containing layer and the first ceramic layer 1 is 9 mm.
[0150] (Comparative Example 4)
[0151] A glass plate 7 is formed by stacking a first ceramic layer 1, a silver-containing layer, and a second ceramic layer 1 on a glass mother plate. In the glass plate 7, the outer edges of the first ceramic layer 1 and the second ceramic layer 1 overlap. The width of the first ceramic layer 1 is 20 mm, and the width of the second ceramic layer 1 is 4 mm. The width of the overlap between the silver-containing layer and the first ceramic layer 1 is 2 mm.
[0152] Evaluation results of the red halo phenomenon
[0153] For each glass panel, when used as window glass, a visual evaluation was performed from the outside of the vehicle (i.e., the surface without the first ceramic layer 1, the silver-containing layer, and the second ceramic layer 1). The results showed that no obvious red halo phenomenon was observed in the glass panels of Examples 1-3 and Comparative Examples 2-4. A significant red halo phenomenon was observed in the glass panel of Comparative Example 1.
[0154] Analysis revealed that in Examples 1 and 2, no red halo phenomenon occurred because the second ceramic layer of glass plates 1 and 2 did not overlap with the silver-containing layer. In Example 3, although the second ceramic layer of glass plate 3 overlapped with the silver-containing layer, the inner edge of the overlapping portion was more than 10 mm outside the inner edge of the first ceramic layer. Therefore, when used as window glass, the red halo phenomenon observed when viewed from the outside of the vehicle was not obvious within the obstruction range of the first ceramic layer. In Comparative Example 1, the second ceramic layer of glass plate 4 overlapped with the silver-containing layer, and because the inner edge of the overlapping portion was only 8.9 mm outside the inner edge of the first ceramic layer, it did not reach more than 10 mm as in Example 3, thus a significant red halo phenomenon was observed.
[0155] Demolding performance evaluation results
[0156] The demolding properties of each glass plate were evaluated, and the results showed that the glass plates of Examples 1-3 and Comparative Examples 1-2 had better demolding properties. The glass plates of Comparative Examples 3-4 had poor demolding properties.
[0157] Analysis revealed that in Examples 1-3, the demolding properties of the glass plates were guaranteed because the width of the second ceramic layer was greater than 5 mm. However, in Comparative Example 3, the demolding properties of the glass plates could not be guaranteed because there was no second ceramic layer (i.e., the width of the second ceramic layer was zero). Furthermore, in Comparative Example 3, the demolding properties of the glass plates could not be guaranteed because the width of the second ceramic layer was less than 5 mm.
[0158] Appearance evaluation results
[0159] The appearance of each glass plate was evaluated, and it was found that Examples 1-3 and Comparative Examples 1, 3-4 had better appearances. Comparative Example 2 had a poor appearance because the silver-containing layer and the first ceramic layer did not overlap, so the gap between the first ceramic layer and the silver-containing layer was visible.
[0160] Finally, it should be understood that the above description of the embodiments and examples is illustrative in all respects and does not constitute a limitation of the present invention. Those skilled in the art can make various improvements without departing from the spirit of the present invention without creative effort. The scope of the present invention is defined by the claims, not by the above embodiments or examples. Furthermore, the scope of the present invention includes all modifications within the meaning and scope equivalent to the claims.
[0161] Industrial availability
[0162] This glass sheet and this laminated glass can be used in various transportation vehicles such as automobiles, ships, trains, airplanes, spacecraft and space stations.
Claims
1. A glass plate comprising... Glass motherboard, First ceramic layer Contains metal layer, Second ceramic layer, in, The metal is silver or a mixture of silver and other metals. The first ceramic layer and the second ceramic layer at least partially overlap when viewed from above. The first ceramic layer contains Bi4Si3O 12 The crystallization ratio of CuCrMnO4, as determined by XRD, ranged from 0.1% to 8.0%. The second ceramic layer is located on the side of the first ceramic layer opposite to the glass substrate, and contains Bi4Si3O. 12 The crystallization ratio of CuCrMnO4, as determined by XRD, was 9.5–30.0%. The crystallization ratio is Bi4Si3O 12 The ratio of CuCrMnO4.
2. The glass plate as described in claim 1, wherein, The crystallinity of the first ceramic layer is 0.1-5.0%, and the crystallinity of the second ceramic layer is 10.0-25.0%.
3. The glass plate as described in claim 1 or 2, wherein, The metal layer does not overlap with the second ceramic layer.
4. The glass plate as described in claim 1 or 2, wherein, When viewed from above, the metal-containing layer at least partially overlaps with the second ceramic layer, and the inner edge of the overlapping portion is located more than 10 mm outside the inner edge of the first ceramic layer.
5. The glass plate as claimed in claim 1, wherein, The width of the first ceramic layer is 10 mm or more.
6. The glass plate as claimed in claim 1, wherein, The width of the second ceramic layer is more than 5 mm.
7. The glass plate as claimed in claim 1, wherein, The metal is silver.
8. The glass plate as claimed in claim 1, wherein, The metal-containing layer comprises two or more layers of silver metal.
9. A laminated glass comprising a glass plate according to any one of claims 1 to 8, a second glass plate, and an interlayer film located between the glass plate and the second glass plate and joining the two glass plates.
10. The laminated glass as claimed in claim 9, wherein, The visible light transmittance of the laminated glass is below 10%.
11. A method for manufacturing a glass plate according to any one of claims 1 to 8, comprising the following steps: 1) The process of providing glass motherboards; 2) The step of applying a first ceramic raw material composition comprising at least bismuth oxide, silicon oxide and Cr2CuO4 to at least a portion of a glass master plate; 3) The process of firing to form the first ceramic layer; 4) The process of forming a metal layer: 5) The step of applying a second ceramic raw material composition comprising at least bismuth oxide, silicon oxide and Cr2CuO4 to at least a portion of the first ceramic layer; 6) The process of firing to form the second ceramic layer.
12. The manufacturing method as described in claim 11, wherein, The firing temperature is 600-670℃.
Citation Information
Patent Citations
Cooling device of engine
JP1985065221A